TREN PEMASARAN JASA SYARIAH: ANALISIS SWOT PADA SEKOLAH AL- AZHAR CAIRO DI KOTA BANDA ACEH - Yusniar, Yusniar (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2024)
Business in the service sector has continued to grow in recent years. It cannot be denied that running a business requires creative innovation. In order to create a new idea, a businessman is required to actively search for relevant information to support creative ideas, including within the scope of service marketing. Al-Azhar Islamic School Cairo Banda Aceh is a branch of the Islamic school Al-Azhar Cairo Indonesia. This school is a school for memorizing the Qur'an which applies the national education curriculum and the Al-Azhar Cairo Banda Aceh religious curriculum and combines education based on IMTAQ (faith and piety) and science and technology (science and technology). The results of the research show that the marketing strategy implemented by Kindergarten Al-Azhar Cairo in competing is by using a 4P marketing mix strategy, namely service strategy, price strategy, place strategy and promotion strategy.